UNWRAPPING GOOGLE PAY'S DIWALI 'LADDOOS' CAMPAIGN: HOW VIRTUAL MARKETING IS TRANSFORMING FESTIVE ENGAGEMENT - Vishnu Ms; P. Radhakrishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The proliferation of digital payments has opened new avenues for virtual marketing, and Google Pay's Diwali 'Laddoos' campaign represents a notable example of leveraging festive occasions to engage users. This study aims to evaluate the virtual marketing strategies employed by Google Pay during its Diwali 'Laddoos' campaign, focusing on how digital engagement techniques were designed to attract and retain users during the festive season. The research examines the role of social sharing and referral incentives in driving user participation and community-driven brand growth. A sample of 100 respondents provided data through structured questionnaires, which were analyzed to draw meaningful insights. The findings indicate high user engagement, satisfaction, and effective use of social sharing and referral incentives. Recommendations for future campaigns include diversifying awareness channels, simplifying participation mechanics, enhancing engagement tactics, boosting social sharing incentives, and optimizing referral programs. The study concludes that Google Pay’s campaign effectively utilized virtual marketing techniques to enhance festive engagement, setting a benchmark for future digital campaigns.